Knowledge and practice of nurses on care of elderly patients in a tertiary care hospital: a cross-sectional study - Dhakal, Pramila; Awale, Shanti; Sankhi, Mukti Nath; Bhatta, Kumari Shanta (International Journal of Research in Medical Sciences, 2026)
Background: The elderly population is continuing to increase in Nepal, leading to the need for skilled and nursing care, particularly in hospital settings. Nurses are important healthcare providers for older adults, and their knowledge and practice related to older adults and care can enhance or reduce from quality of care of elderly. The purpose of this study was to assess the knowledge and practice of care in elderly patients. The study was conducted at tertiary care hospital, Nepal. Methods: Between November 2023 and April 2025, a cross-sectional analysis study was done at tertiary care Hospital. Using non-probability methods, 218 nurses were included in the study. Researcher developed self-administered questionnaire was used for knowledge, and researcher developed observation checklist was used to assess the practice of nurses. Using SPSS version 16, we used descriptive and inferential statistics methods for data analysis. Results: The results showed that 89.9% of the nurses had acceptable knowledge of elderly care, while 10.1% exhibited poor knowledge. For practice, only 63.3% of the immobilised elderly patients had their position changed regularly, and only 10% received pressure ulcer care. There was no association between sociodemographic characteristics and knowledge level. Conclusions: While most of the nursing staff had adequate knowledge about the elderly care, their practice was low in providing care, most notably pressure ulcer prevention and catheter care. The authors suggested that education and consistent use of the guidelines are needed in the elderly care setting.